SOCIOLOGICAL ANALYSIS OF SEXUAL SATISFACTION IN INDIVIDUALS WITH MARRIAGE AGE UNDER TEN YEARS OLD - Trias Novita Ellsadayna (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Studies on sexual satisfaction in individuals has been dominated by psychological perspectives. However, sexual satisfaction can also be studied comprehensively using a sociological approach. This article intends to determine social factors that influence the sexual satisfaction of individuals with marriage age under ten (10) years old. Research subjects were obtained using the criteria of individuals who have been married for ten years, age range from 25 - 39 years old, and number of informants (n) = 40. The study used the NSSS (New Sexual Satisfaction Scale) instrument with a Cronbach's alpha of 0.97. The results showed that the average male sexual satisfaction was 74.95, and the female sexual satisfaction average was 64.44. These data show that men have higher sexual satisfaction than women. Social construction shapes women as objects of male sexual satisfaction. Another influenced sociological aspect is the type of work and its social role in the family. Individuals who work in working sectors with high pressure and low-income are potential to have low sexual satisfaction. Meanwhile, individuals who work at working situation that are more relaxed and flexible in terms of time and place, having high potential sources of income tend to have a high sexual satisfaction. The results showed that the average sexual satisfaction of individuals with a marriage age range from three to ten years is 43.49% and it is included in a very low category. It can be concluded that individuals with the marriage age which felt sexual dissatisfaction are those under ten years during the pandemic.Kepuasan seksual pada individu selama ini banyak didominasi kajian Psikologi. Meski demikian, kepuasan seksual dapat dikaji dengan menggunakan pendekatan Sosiologis. Artikel ini bermaksud untuk mengetahui faktor-faktor yang mempengaruhi kepuasan seksual individu dengan usia pernikahan di bawah sepuluh (10) tahun. Penelitian ini menggunakan metode kuantitatif-deskriptif dengan teknik pengumpulan data dilakukan melalui purposive sampling terhadap 68 individu dengan rentang usia 25-39 tahun, dan telah menikah maksimal sepuluh (10) tahun. Penelitian ini menggunakan instrument NSSS (New Sexual Satisfaction Scale) dengan Cronbach's alpha 0,97. Hasil Penelitian menunjukkan rata-rata kepuasan seksual laki-laki adalah 74.42 dan rata-rata kepuasan seksual perempuan adalah 70.83. Meskipun nilai rata-rata kepuasan perempuan dan laki-laki masuk dalam kategori cukup puas. Namun, dapat terlihat laki-laki memiliki kepuasan seksual yang lebih tinggi dari perempuan. Hal ini disebabkan adanya konstruk sosial yang membentuk perempuan sebagai objek dari kepuasan seksual laki-laki. Aspek sosiologi lain yang mempengaruhi adalah tipe pekerjaan dan peran sosialnya di keluarga. Individu yang bekerja di sektor pekerjaan dengan tekanan tinggi dan potensi pendapatan yang rendah memiliki kepuasan seksual yang rendah. Sedangkan pada individu dengan tipe pekerjaan yang santai dan fleksibel dari segi waktu dan tempat serta memiliki potensi sumber pendapatan tinggi dan lebih dari satu memiliki kepuasan seksual yang tinggi.